MOTIVATION TO LEARN PUBLIC HIGH SCHOOL STUDENTS AND BOARDING SCHOOLS DURING ONLINE LEARNING - Adhetya Cahyani; Nur Imam Mahdi; Ro'fah (Sunan Kalijaga International Journal on Islamic Educational Research, 2021)
This study aims to determine whether there are differences in learning motivation between general high school and high school of Islamic boarding school during online learning. The population of the study were all high school students, both general and Islamic boarding schools who were taking online learning. The research method used is a quantitative approach. The data collection method uses a questionnaire that is distributed using google form. The data analysis method uses the Independent Sample t Test technique. The data collected was 250 people, divided by 149 general high school students and 101 high school students of Islamic boarding schools. After testing the hypothesis using the Independent Sample t Test, it is found that the hypothesis is accepted, there is a significant difference in learning motivation between general high school students and Islamic boarding schools with a significance value of 0.033 and 0.027. Then also the results obtained that the mean value of high school students of Islamic boarding schools is higher, namely 53.09 compared to the mean value of general high school students which is 51.27. This means that the learning motivation of Islamic boarding school high school students is higher than general high school students during the online learning process.